MERDEKA BELAJAR DI TENGAH PANDEMI C-19 - Ahmad Wahib (Jurnal Paradigma, 2022)
The “Merdeka Belajar” program, if linked to the Merdeka Learning Program initiated by the Minister of Education and Culture of the Republic of Indonesia, is a free choice that can be given to students to suit their interest and character. Some teachers apply conservative teaching methods. They provide step-by-step instructions so that both students and students are like being bribed with a spoon. Everyone has a different way of learning. The pandemic has been able to paralyze various sectors. One of those affected is the education sector. The arrival of the corona has caused the world of education to be closed at home. Work from home (WFH) is the best solution so that educational activities can continue.